Implementasi Kebijakan Kompensasi dan Benefit serta Implikasinya pada Kepuasan Kerja Karyawan di Laris Ambarawa - Mencari Lase; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to analyse the implementation of compensation and benefits policies and their implications for employee job satisfaction at Laris Ambarawa, Semarang Regency. The problem focuses on how compensation and benefits policies are implemented in organizational practice and how they are perceived by employees in shaping job satisfaction. To approach this issue, the study applies human resource management theory, particularly compensation and job satisfaction theories, emphasising fairness, motivation, and job security. Data were collected through in-depth interviews, observation, and documentation, and analysed qualitatively using thematic analysis. The findings reveal that the compensation system has been implemented through position-based salaries, performance-based incentives, holiday allowances, and benefits such as social security and annual leave. These policies contribute to employees’ sense of security, loyalty, and organisational commitment, although greater transparency in performance evaluation is still required. This study concludes that job satisfaction is influenced not only by the amount of compensation but also by the clarity of the system, consistency of implementation, and perceived fairness of policy execution.